Change in Action: From Reading to Surfing - Ruth Breeze (Networks: An Online Journal for Teacher Research, 2002)
This article describes the development of a course in English language for undergraduate students of journalism in Spain. The course was shaped by an initial cycle of action research, but it was subsequently remodelled through a further research cycle in order to cater for changing students in a changing world. It is envisaged that this course may undergo many further cycles of change, which is healthy for the institution, teachers, and students alike. The action research paradigm provides a useful framework within which change can be processed and growth fostered. The project described here is of interest in that it is paradigmatic for our professional practice as teachers in the twenty-first century.